Solidification of Sand for Strength Improvement - Legrans, Roski R. I. (TEKNO, 2015)
Several investigations have used geopolymer to increase the strength of soft clay. This research has used the Electric Arc Furnace (EAF) slag, a byproduct from the process of producing steel, as the prime material of geopolymer and activator to make the geopolymer paste to solidified the sand. Two types of treatment were used which were distinguished by the type activator. Its objective is to study the effect of EAF slag-based geopolymer of solidified sand through the relationship between the strength (qu) and both the curing period (t) and the mixture ratio (d). The results of the research give conclusions that the mixture ratio provides a significant effect to the strength of improvement solidified sand (p<0,01 and p<0,05) than the curing period(p>0,05). The highest strength is obtained at the ratio of 50 % among designated mixture ratio, which also delivers the strength of hard soil (over 400 kPa). Â Keywords : solidification, sand, geopolymer, EAF slag